The unique reactivity of 5,6-unsubstituted 1,4-dihydropyridine in the Huisgen 1,4-diploar cycloaddition and formal [2 + 2] cycloaddition - Chen, Xiu-Yu; Zheng, Hui; Han, Ying; Sun, Jing; Yan, Chao-Guo (Beilstein Journal of Organic Chemistry, 2023)
The three-component reaction of isoquinolines, dialkyl acetylenedicarboxylates, and 5,6-unsubstituted 1,4-dihydropyridines in acetonitrile at room temperature afforded functionalized isoquinolino[1,2-f][1,6]naphthyridines in good yields and with high diastereoselectivity. More importantly, the formal [2 + 2] cycloaddition reaction of dialkyl acetylenedicarboxylates and 5,6-unsubstituted 1,4-dihydropyridines in refluxing acetonitrile gave unique 2-azabicyclo[4.2.0]octa-3,7-dienes as major products and 1,3a,4,6a-tetrahydrocyclopenta[b]pyrroles as minor products via further rearrangement.
Keywords: 1,4-dihydropyridine; electron-withdrawing alkyne; formal [2 + 2] cycloaddition; Huisgen's 1,4-dipole; isoquinoline; isoquinolino[1,2-f][1,6]naphthyridine